Using data from the Living Standards Measurement Study (LSMS) (non-food consumption data) to assess dietary intake and its determinants and monitor dietary changes - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
Methodology is developed and preliminary results presented in different fora including the ANH Academy, Tropentag2018, Economist meeting in Nigeria 2019. Final manuscripts (based on data Ethiopia and Nigeria) submitted to scientific papers and in review phase.